Systemic vasculitis and atypical infections: report of two cases. Issue 887 (1st September 1999) - Chakravarty, Kuntal; Merry, Peter
Abstract : Two cases of systemic vasculitis are described; one presenting with adult Henoch-Schonlein purpura secondary to a concomitant Chlamydia infection and the other with leucocytoclastic vasculitis and mesangioproliferative glomerulonephritis secondary to a recent parvovirus B19 infection. Association of chlamydial infection has not previously been described with Henoch-Schonlein purpura and this infection should, perhaps, be added to the list of aetiologies of this disease. Parvovirus B19 causing significant urinary sediment abnormalities associated with mesangioproliferative glomerulonephritis and leucocytoclastic vasculitis has also not been described previously.